2009
DOI: 10.1002/jbm.a.32681
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo testing of novel ultrathin PCL and PCL/PLA blend films as peripheral nerve conduit

Abstract: In an attempt to obviate the drawbacks of nerve autograft, ultrathin microporous biodegradable PCL and PCL/PLA films were tested for their compatibility with motor neuron-like NG108-15 cells and primary Schwann cells. Data obtained from MTS colorimetric and DNA fluorimetric assays showed that both cell lines readily attached and proliferated on these materials. Images taken using scanning electron microscope and fluorescence microscope confirmed these observations. Enhanced cell-surface interaction was achieve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
36
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 47 publications
2
36
0
Order By: Relevance
“…These observations would be explained by the fact that in vitro dASCs have also been observed to align in a highly polarized manner along the grooves, which may also happen for Schwann cells in the inner lumen of the conduits, possibly due to the topographical guidance cues in the material surfaces. Nerve regeneration through micropitted conduits was seen in previous studies, 2 and the present results show an improvement of the regeneration obtained using grooved PCL/PLA conduits, pointing to the effects of surface morphology on the regenerating cells. Our results are also consistent with those of other groups, who showed that PLA conduits with microgrooves on the inner surface improved peripheral nerve regeneration when compared with smooth conduit controls.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…These observations would be explained by the fact that in vitro dASCs have also been observed to align in a highly polarized manner along the grooves, which may also happen for Schwann cells in the inner lumen of the conduits, possibly due to the topographical guidance cues in the material surfaces. Nerve regeneration through micropitted conduits was seen in previous studies, 2 and the present results show an improvement of the regeneration obtained using grooved PCL/PLA conduits, pointing to the effects of surface morphology on the regenerating cells. Our results are also consistent with those of other groups, who showed that PLA conduits with microgrooves on the inner surface improved peripheral nerve regeneration when compared with smooth conduit controls.…”
Section: Discussionsupporting
confidence: 85%
“…[1][2][3] The blend of these polymers has been studied to tailor crucial properties, including mechanical strength and hydrophobicity/hydrophilicity. 4 We have previously reported that ultrathin PCL films and PCL/PLA blended films with a micropitted surface are able to support the attachment and growth of the NG108-15 neuronal cell line and Schwann cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it provides an excellent substrate for guided cell migration and axonal growth, being an efficient alternative to peripheral nerve autografting (Bockelmann et al, 2011;Pierucci et al, 2008;Sun & Downes, 2009;Sun et al, 2010;Yu et al, 2011). Nanometric supports have also been implemented to promote growth and development of neurons and non-neural cells (Mattson, Haddon, & Rao, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…If toxic by-products are released during degradation of a biomaterial, for example, the local healthy tissue is not preserved, and tissue regeneration will This is an interesting point regarding the use of some polymers such as polyglycolic or polylactic acid (PLA), which tend to degrade faster in vivo 9,10 in comparison to other aliphatic polymers such as polycaprolactone (PCL), which remains for a longer time in the body after implantation. 11,12 By dissolving in the surrounding fluid, bioactive glasses also resorb in vivo. 6,13,14 Thus, by combining these two families of materials, fully bioresorbable scaffolds with remarkable mechanical and bioactive properties can be produced.…”
Section: Introductionmentioning
confidence: 99%